2018
DOI: 10.1038/s41556-018-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectrin is a mechanoresponsive protein shaping fusogenic synapse architecture during myoblast fusion

Abstract: Spectrin is a membrane skeletal protein best known for its structural role in maintaining cell shape and protecting cells from mechanical damage. Here, we report that α/β-spectrin (β is also called karst) dynamically accumulates and dissolves at the fusogenic synapse between fusing Drosophila muscle cells, where an attacking fusion partner invades its receiving partner with actin-propelled protrusions to promote cell fusion. Using genetics, cell biology, biophysics and mathematical modelling, we demonstrate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 63 publications
4
69
0
Order By: Relevance
“…This result confirmed that changes in spectrin density based on fluorescence intensity could be observed upon drug perturbations by our approach (Figure 4 A-B). Since microtubules (MT) have also been proposed to control βII-spectrin and βV-spectrin dynamics at cell-cell junctions (Jenkins, He and Bennett, 2015; Duan et al ., 2018), we investigated their role in βII-spectrin recruitment to the cell cortex. Upon MT depolymerization, even at early time points (5 minutes), spectrin density increased by almost 20% (Figure 4 A-B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result confirmed that changes in spectrin density based on fluorescence intensity could be observed upon drug perturbations by our approach (Figure 4 A-B). Since microtubules (MT) have also been proposed to control βII-spectrin and βV-spectrin dynamics at cell-cell junctions (Jenkins, He and Bennett, 2015; Duan et al ., 2018), we investigated their role in βII-spectrin recruitment to the cell cortex. Upon MT depolymerization, even at early time points (5 minutes), spectrin density increased by almost 20% (Figure 4 A-B).…”
Section: Resultsmentioning
confidence: 99%
“…Based on different mechanical perturbations of the PM, we propose that spectrin is maintained globally at a constant ratio with the lipid bilayer. Locally, it reacts instead to intrinsic cues, such as PM collapse (Figure 7 I, zone VII), or to external perturbations, such as cell-cell fusion (Duan et al ., 2018). These reactions correspond to a meshwork condensation rather than de-novo recruitment, as a self- and cell-protective mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells, radial contractility of subcortical actin (Duan et al, 2018) or actin rings (Gormal et al, 2015) is regulated by mechanosensory NM-II, which has the ability to convert ATP into mechanical force. Recently, the activated form of NM-II light chain (p-MRLC) was shown to distribute with a similar periodicity and largely overlap with the actin MPS at the AIS (Berger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our FRAP result showing that Dlg can flow out of the SSR even in wild-type body walls. A recent study of the role of the spectrin cytoskeleton in Drosophila myoblast fusion demonstrates another function for spectrin corralling in muscle development: the corralling of the cellular adhesion molecules Dumbfounded and Antisocial in embryonic myoblasts (Duan et al, 2018). In wild-type embryos Dumbfounded and Antisocial are tightly clustered but become dispersed in a/bH-spectrin double mutants.…”
Section: A Corralling Model For Spectrin Regulation Of Nmj Developmentmentioning
confidence: 99%